Analisis Kesantunan Berbahasa Mahasiswa di Lingkungan Kampus STIT NU Al-Mahsuni Lombok Timur - Ade Jauhari (Institut Agama Islam Negeri Curup, 2024)
Language politeness is one aspect of language that must receive serious attention in communicating in religious universities. The application of language politeness is a necessity in order to maintain the cultural values ​​of language politeness which must be possessed by every religious college student. This research aims to describe the form of compliance principles of language politeness of the college student speech in the campus environment in STITNU Al-Mahsuni East Lombok and describe strategies used in the realization of language politeness of the college student speech in the campus environment in STITNU Al-Mahsuni East Lombok. This research uses qualitative descriptive research. The data were collected through simak bebas libat cakap technique, recording and taking notes. The data analysis used the ekstralingual identity method. The results of the research show that college student speech in the campus environment in STITNU Al-Mahsuni East Lombok has complied with the maxims of the tact, generosity, approbation, agreement, modesty and sympathy. The strategies used by college student in the realization language politeness are by applying positive politeness strategies and negative politeness strategies. The conclusion of this research is that students' compliance with the principles of politeness is dominated by maxims of wisdom to minimize harm that could occur to the person they are speaking to. The strategy used in student speech is dominated by giving praise to the person speaking so that when they start the speech, it will feel more harmonious. The use of the principles of language politeness also provides new insights for students in speech acts among fellow academics.